Analisis Keamanan Tebing Pada Areal Bekas Tambang Di Desa Semaya, Kecamatan Randudongkal, Kabupaten Pemalang - Rinal Khaidar Ali; Najib Najib; Adam Kahfi Mulyadi (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2019)
Mining activities has become increasingly widespread in recent years, especially people’s mining, thatjust concerned about the result and not paying attention to the environmental factors.This is causedthe post mining area’s destruction and environmental degradation potential. For this reason, the slopesafety factor enhancement analysis on the post mining area in Semaya Village, Randudongkal Sub-District, Pemalang Regency is needed. Slope stability analysis using Slide 6.0 software to identify thecondition of post mining area from the results of undisturbed sample (UDS) laboratory data.Laboratory testing includes several aspects including water content, weight, specific gravity, grain size,atteberg limit test, and direct shear test. The value of the safety factor is 1,441, the value is in the safecategory because it passes the minimum value limit of the safety factor which is 1.25, this result isobtained from the terracing modeling.